Strengthening biodiversity conservation and One Health through ranger monitoring of wildlife health in protected areas - Diego Montecino‐Latorre; Sarah H. Olson; Emily Denstedt; Luis Guerra; Paulo Colchao‐Claux; Lucy Keatts; Aristide Andrianarimisa; Lovasoa Rabarisoa; Manfredo Martínez; Sophalrachana Kong; Devin Vorn; Zeveyda Jhancy Segura; et al. (Conservation Biology, 2026)
The lack of wildlife health (WH) surveillance systems leaves critical gaps in biodiversity conservation and One Health protection. Integrating rangers patrolling protected areas (PAs) into WH monitoring represents a cost‐effective and scalable opportunity to address these gaps at key human–wildlife interfaces and nature strongholds. For the past 2.5 years, organizations across 4 countries have collaborated to pilot this integration. The approach involved establishing a practical definition of health event for rangers patrolling PAs, developing a referential form tailored for rangers to document these events, training key country actors to identify and record health events on this form, merging this form with local forms used by rangers to record other events of interest observed during their patrols (e.g., illegal logging), and training rangers to identify and document health events with the modified local form. We examined 4 case studies involving dozens of PAs in different countries with different languages and local partners. The recording of health events was supported by the Spatial Monitoring And Reporting Tool, SMART, which provides the modified form for rangers on mobile devices and enabled standardized recording of events. Currently, over 200 rangers across more than 50 PAs have been trained, and more than 1000 health events have been recorded. This provides early evidence that rangers could enhance WH monitoring and strengthen biodiversity conservation, ultimately fostering One Health. This initiative lays important groundwork for overcoming key barriers (e.g., lack of personnel and funding) to establishing functional WH surveillance systems in PAs. Still, specific data infrastructure, human resources, and institutional support are needed. It will be important to evaluate the limitations of ranger‐collected data and align monitoring goals with the capabilities of rangers and data managers. Expansion to additional PAs is planned, alongside efforts to integrate ranger‐collected data into multisectoral One Health frameworks.

Critical mineral recovery and carbon storage potential at the Tamarack intrusive complex - Harshvardhan Chopra; C. Heath Stanfield; Madeline F. Bartels; Nabajit Lahiri; Jose Marcial; Emily T. Nienhuis; Inna Mudrovska; Mathieu Fillion; Robert Rush; Martin Sauvé; Tom Hunt; Niki Morton; et al. (International Journal of Greenhouse Gas Control, 2026)

Tree ferns on the move: patterns of movement and current introduction status of Cyatheales species around the world - Megan L. van den Berg; David M. Richardson; Emily J. McCulloch-Jones; Mathieu Rouget; Tamara B. Robinson (Biological Invasions, 2026)
Tree ferns (order Cyatheales) have been moved from their native ranges for more than two centuries, and the number of species introduced to new countries has recently increased rapidly. However, no comprehensive global list of alien tree ferns exists. Botanical garden collections and the Global Biodiversity Information Facility database were examined, and a systematic literature review was conducted to collect information on tree fern introduction dates, locations and impacts in non-native ranges. Overall, 158 species out of 795 Cyatheales species (c. 20%) were found to have been introduced. The earliest documented introduction occurred in 1789 when Dicksonia arborescens L’Hér. was moved from St Helena Island to the United Kingdom. Tree fern introductions are biased in favour of well-developed countries with historical exploration in regions with rich native tree fern floras. Five species have naturalised ( Alsophila australis in Sri Lanka; Alsophila speciosa in Madagascar; Sphaeropteris excelsa in the United States of America; Sphaeropteris medullaris in Madeira (Portugal); and Lophosoria quadripinnata in Fiji, French Polynesia and the United States of America). Two species are invasive: Sphaeropteris cooperi in the Azores (Portugal), Hawaiian Is. (USA), Mauritius, Réunion Isl. (France) and South Africa; and Dicksonia antarctica in the Azores (Portugal) and Sri Lanka. The extensive history of tree-fern movement has radically altered the global distribution of the order Cyatheales, creating substantial invasion debt. The 151 alien (not yet naturalised) species represent a substantial capacity for future invasion. This list can inform monitoring of the distribution of already introduced species to support prevention of further invasions.

Lower-limb physical function is associated with executive function in frail older adults - Myles W. OBrien; Shirko Ahmadi; Pierre Faivre; Isadora Quirion; Vicky Bouffard-Levasseur; Tina Emond; Anik Lang; Emily MacDonald; Olivier Dupuy; Anne Sophie Champod; Mathieu Bélanger; Said Mekari (GeroScience, 2026)

A digital twin integrating multi-objective optimization to support fryer operators in managing potato crisps production - Manon Perrignon; Mathieu Emily; Mélanie Munch; Paul Debuire; Romain Jeantet; Thomas Croguennec (Journal of Food Engineering, 2026)

The invaded range of the tree fern Sphaeropteris cooperi is predicted to shrink in two southern hemisphere biodiversity hotspots - Megan L. van den Berg; Geethen Singh; Emily J. McCulloch-Jones; Mathieu Rouget; David M. Richardson; Tamara B. Robinson (South African Journal of Botany, 2025)

Machine learning for predicting industrial performance: Example of the dry matter content of emmental-type cheese - Manon Perrignon; Mathieu Emily; Mélanie Munch; Romain Jeantet; Thomas Croguennec (International Dairy Journal, 2025)

The multi-objective data-driven approach: A route to drive performance optimization in the food industry - Manon Perrignon; Thomas Croguennec; Romain Jeantet; Mathieu Emily (Trends in Food Science & Technology, 2024)

Behavioral Treatment for Speech and Language in Primary Progressive Aphasia and Primary Progressive Apraxia of Speech: A Systematic Review - Lisa D. Wauters; Karen Croot; Heather R. Dial; Joseph R. Duffy; Stephanie M. Grasso; Esther Kim; Kristin Schaffer Mendez; Kirrie J. Ballard; Heather M. Clark; Leeah Kohley; Laura L. Murray; Emily J. Rogalski; et al. (Neuropsychology Review, 2024)
Primary progressive aphasia (PPA) and primary progressive apraxia of speech (PPAOS) are neurodegenerative syndromes characterized by progressive decline in language or speech. There is a growing number of studies investigating speech-language interventions for PPA/PPAOS. An updated systematic evaluation of the treatment evidence is warranted to inform best clinical practice and guide future treatment research. We systematically reviewed the evidence for behavioral treatment for speech and language in this population. Reviewed articles were published in peer-reviewed journals through 31 May 2021. We evaluated level of evidence, reporting quality, and risk of bias using a modified version of the American Speech-Language Hearing Association (ASHA) Levels of Evidence, an appraisal point system, additional reporting quality and internal/external validity items, and, as appropriate, the Single Case Experimental Design Scale or the Physiotherapy Evidence Database – PsycBITE Rating Scale for Randomized and Non-Randomized Controlled Trials . Results were synthesized using quantitative summaries and narrative review. A total of 103 studies reported treatment outcomes for 626 individuals with PPA; no studies used the diagnostic label PPAOS. Most studies evaluated interventions for word retrieval. The highest-quality evidence was provided by 45 experimental and quasi-experimental studies (16 controlled group studies, 29 single-subject designs). All ( k = 45/45) reported improvement on a primary outcome measure; most reported generalization ( k = 34/43), maintenance ( k = 34/39), or social validity ( k = 17/19) of treatment for at least one participant. The available evidence supports speech-language intervention for persons with PPA; however, treatment for PPAOS awaits systematic investigation. Implications and limitations of the evidence and the review are discussed.

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

High‐resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Mathieu Quenu; Emily J. Judd; Mary Morgan‐richards; Steven A. Trewick; Katherine Holt; Jonathan Tyler; Andrew M. Lorrey (Journal of Quaternary Science, 2023)
The stable oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high‐resolution isotopic profiles of nine modern land snails of the genus Placostylus , collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ 18 O shell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ 18 O shell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ 18 O shell values. Snails from New Zealand had, on average, slightly higher δ 13 C shell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ 13 C shell values, indicating potential shifts in diet through to maturity.

Cognitive and behavioral effects of whole brain conventional or high dose rate (FLASH) proton irradiation in a neonatal Sprague Dawley rat model - Michael Williams; Chiho Sugimoto; Samantha Regan; Emily Pitzer; Adam Fritz; Mathieu Sertorio; Anthony Mascia; Ralph Vatner; John Perentesis; Charles Vorhees (Neurotoxicology and Teratology, 2023)

WildHealthNet: Supporting the development of sustainable wildlife health surveillance networks in Southeast Asia - Mathieu Pruvot; Emily Denstedt; Alice Latinne; Alice Porco; Diego Montecino-Latorre; Kongsy Khammavong; Phonesavanh Milavong; Souchinda Phouangsouvanh; Manoly Sisavanh; Nguyen Thi Thanh Nga; Pham Thi Bich Ngoc; Vo Duy Thanh; et al. (Science of The Total Environment, 2023)

A field indicator for rhizosphere effect monitoring in arable soils - Sébastian Mira; Mathieu Emily; Christophe Mougel; Morgane Ourry; Edith Le Cadre (Plant and Soil, 2022)

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Light at night reduces digestive efficiency of developing birds: an experiment with king quail - Tuul Sepp; Emily Webb; Richard K. Simpson; Mathieu Giraudeau; Kevin J. McGraw; Pierce Hutton (The Science of Nature, 2021)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Establishing IUCN Red List Criteria for Threatened Ecosystems - JON PAUL RODRÍGUEZ; KATHRYN M. RODRÍGUEZ‐CLARK; JONATHAN E. M. BAILLIE; NEVILLE ASH; JOHN BENSON; TIMOTHY BOUCHER; CLAIRE BROWN; NEIL D. BURGESS; BEN COLLEN; MICHAEL JENNINGS; DAVID A. KEITH; EMILY NICHOLSON; et al. (Conservation Biology, 2011)
The potential for conservation of individual species has been greatly advanced by the International Union for Conservation of Nature's (IUCN) development of objective, repeatable, and transparent criteria for assessing extinction risk that explicitly separate risk assessment from priority setting. At the IV World Conservation Congress in 2008, the process began to develop and implement comparable global standards for ecosystems. A working group established by the IUCN has begun formulating a system of quantitative categories and criteria, analogous to those used for species, for assigning levels of threat to ecosystems at local, regional, and global levels. A final system will require definitions of ecosystems; quantification of ecosystem status; identification of the stages of degradation and loss of ecosystems; proxy measures of risk (criteria); classification thresholds for these criteria; and standardized methods for performing assessments. The system will need to reflect the degree and rate of change in an ecosystem's extent, composition, structure, and function, and have its conceptual roots in ecological theory and empirical research. On the basis of these requirements and the hypothesis that ecosystem risk is a function of the risk of its component species, we propose a set of four criteria: recent declines in distribution or ecological function, historical total loss in distribution or ecological function, small distribution combined with decline, or very small distribution. Most work has focused on terrestrial ecosystems, but comparable thresholds and criteria for freshwater and marine ecosystems are also needed. These are the first steps in an international consultation process that will lead to a unified proposal to be presented at the next World Conservation Congress in 2012.